Spatial and temporal distribution of bacterial community and heavy metals composition of sediments along Pahang River - Mohd Huzaimi bin Mohd Amin (Kulliyyah of Science, International Islamic University Malaysia, 2017)
Rapid expanding of industrialization and urbanization along the Pahang River requires continuous monitoring in order to know the current status and to protect this ecosystem. This study aimed to determine spatial and temporal distribution of bacterial community, physicochemical parameters, sediment grain size characteristics and heavy metals composition in Pahang River's sediments. The bacterial community in sediments along the Pahang River was determined using culture-based method. The bacterial colony forming unit (CFU) range was found between 1527 ± 65 and 16147 ± 226 CFU/g during pre-monsoon while 1013 ± 39 and 28827 ± 418 CFU/g during post-monsoon. The identified bacteria genera in the river sediments were Bacillus, Enterobacter, Escherichia, Serratia, Aeromonas, Pseudomonas and Staphylococcus. The physicochemical parameters were determined using HYDROLAB multiprobes DataSonde® 5. The temperature was found between 24.671 ± 0.516 and 31.171 ± 0.314 °C, pH ranged between 6.639 ± 0.040 to 9.042 ± 0.028, salinity ranged between 0.000 to 30.172 ± 0.271 ppt, dissolved oxygen (DO) ranged between 1.698 ± 0.035 to 9.383 ± 0.508 mg L-1 and the depth ranged between 0.352 ± 0.156 to 973 ± 3.009 m. The sediment grain size consists of coarse or very coarse sand at all stations. The heavy metal concentrations were determined by using Inductively Coupled-Plasma Mass Spectrometry (ICP-MS). The dry weight concentration of arsenic ranged between 4.387 ± 0.586 to 15.922 ± 8.738 µg g-1 during pre-monsoon while 3.989 ± 0.758 to 11.336 ± 6.748 µg g-1 during post-monsoon, cobalt was found between 1.730 ± 0.318 and 4.569 ± 0.586 µg g-1 during pre-monsoon while 1.476 ± 0.063 and 4.620 ± 0.951 µg g-1 during post-monsoon, copper ranged between 1.182 ± 0.510 to 10.722 ± 5.664 µg g-1 during pre-monsoon and 0.900 ± 0.222 to 6.514 ± 3.749 µg g-1 during post-monsoon, zinc was found between 7.964 ± 4.857 and 26.289 ± 2.636 µg g-1 during pre-monsoon while 8.187 ± 3.010 and 28.347 ± 15.665 µg g-1 during post-monsoon, chromium from 3.250 ± 2.065 to 21.950 ± 6.904 µg g-1 during pre-monsoon while 4.719 ± 2.811 to 20.664 ± 3.548 µg g-1 during post-monsoon, cadmium was found between 0.019 ± 0.008 and 0.116 ± 0.045 µg g-1 during pre-monsoon while 0.024 ± 0.017 and 0.403 ± 0.053 µg g-1 during post-monsoon, lead ranged between 8.024 ± 3.542 to 20.660 ± 3.126 µg g-1 during pre-monsoon and 8.696 ± 3.433 to 17.887 ± 2.537 µg g-1 during post-monsoon, nickel was found between 3.113 ± 0.825 and 10.137 ± 9.626 µg g-1 during pre-monsoon while 3.284 ± 1.221 and 8.073 ± 4.519 µg g-1 during post-monsoon, aluminium ranged between 42388.889 ± 8940.610 to 93588.889 ± 10347.938 µg g-1 during pre-monsoon and 50846.667 ± 13703.594 to 84091.111 ± 34682.522 µg g-1 during post-monsoon. There were significant difference of bacterial CFU and all physicochemical parameters among sampling stations and seasons. For heavy metals composition, there were significant differences for all studied heavy metals between sampling stations while for sampling seasons, the differences were only found in arsenic, cadmium, cobalt and aluminium concentrations. The correlation results showed that the bacterial community distribution was influenced by the temperature, pH, DO, salinity and cadmium concentrations while the other parameters showed no significant correlation towards bacterial community distribution. As conclusion, the present study has provided the current condition of Pahang River to facilitate in the management and conservation of the river ecosystem in the future.